y = 3 in the equation 31 = 4 - 9y
Solve for y.
31 - 4 = 4 - 9y - 4
Simplify
27 = 9y
Divide both sides by 9 to get the term y by itself on one side of the equation.
27 / 9 = 9y / 9
Simplify
3 = y
73y + 144y + 49y=266y
35xy / 49y in simplest form is 5x/7
Then A = 31, b = 31 and c = 31/15 = 2.066...
(7y + 2)(7y - 2)
simplify the expression 16+7y-8 rewrite as 7(y-8)7•y= 7y 7•8= 56 7y-56 = -49y answer= 16+ (-49y)
62
31 x 1
31 times 31
it equals 283. (:
The mathematical statement 31 plus 21 equals 52 as a total.
1 x 31, 31 x 1
8x - 7y = 7 (A)7x + 8y = 8 (B)7*(A): 56x - 49y = 498*(B): 56x + 64y = 648*(B)-7*(A): (64+49)*y = 64-49=> 113y = 15=> y = 15/113